INVESTIGATING THE IMPACT OF AHASLIDES ON STUDENT ENGAGEMENT IN THE ENGLISH CLASSROOM: A CASE STUDY OF YOUNG EFL LEARNERS - Diana Achmad; Asnawi Muslem; Yunisrina Qismullah Yusuf; Siti Sarah Fitriani (Politeknik Negeri Jakarta, 2025)
English language acquisition is essential to be developed from a young age. However, most elementary school students learning English as a Foreign Language (EFL) continue to experience numerous challenges. These are usually the result of instructional strategies that do not fully align with the requirements of 21st-century skills. Instruction is often teacher-centred, with not much peer interaction and hardly any utilization of technology to support meaningful learning experiences. This condition highlights the need to explore how interactive technologies can improve student engagement and make learning more meaningful and learner-centered. Therefore, the aim of this study is to investigate the impact of student engagement in an English private classroom in Banda Aceh where the application of the interactive technology AhaSlides was integrated in the learning process. A case study design was employed, with six students aged between 10-11 years old. Observation sheets were used as data collection instrument to assess student engagement during the lessons taught by the teacher with and without the integration of technology, AhaSlides. The findings indicate an increase in student engagement after the teacher integrated AhaSlides in the learning process in terms of positive body language, consistent focus, verbal participation, confidence, and fun and excitement. This confirms that technology use can enhance learner engagement, which is essential to the success of English language learning.